2007
DOI: 10.1016/j.amjcard.2007.03.104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Prognostic Significance of the Electrocardiographic QRS/T Angles in Predicting Incident Coronary Heart Disease and Total Mortality (from the Atherosclerosis Risk In Communities Study)

Abstract: Spatial QRS/T angle and spatial T-wave axis were shown to be strong independent predictors of incident coronary heart disease (CHD) and total mortality, but they are not routinely available. We evaluated whether frontal plane QRS/T angle, easily obtained as the difference between frontal plane axes of QRS and T, provides a suitable substitute for spatial QRS/T angle as a risk predictor. Our study consisted of 13,973 participants from the ARIC Study. Outcome variables were incident CHD and total mortality durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 28 publications
(32 reference statements)
5
119
1
5
Order By: Relevance
“…Although several reports have shown that findings on the routine ECG are associated with future HF events,8, 9, 10, 11, 12, 13, 14, 15, 16, 17 few have explored whether ECG predictors vary in their ability to distinguish between HFrEF and HFpEF. A recent examination from the Framingham Heart Study has shown that left ventricular hypertrophy and left bundle‐branch block are associated with HFrEF and that atrial fibrillation is associated with HFpEF 28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several reports have shown that findings on the routine ECG are associated with future HF events,8, 9, 10, 11, 12, 13, 14, 15, 16, 17 few have explored whether ECG predictors vary in their ability to distinguish between HFrEF and HFpEF. A recent examination from the Framingham Heart Study has shown that left ventricular hypertrophy and left bundle‐branch block are associated with HFrEF and that atrial fibrillation is associated with HFpEF 28.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that several markers detected on the routine ECG are associated with future HF events8, 9, 10, 11, 12, 13, 14, 15, 16, 17; however, it is currently unknown if a differential risk profile exists for these ECG markers in the prediction of HFrEF versus HFpEF. The ability to identify specific predictors for HFrEF and HFpEF is an important step to target appropriate preventive strategies for each HF subtype.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the mean spatial QRS-T angle is, in general, higher for males than females [12]. There is a wide spectrum of normal limits for spatial QRS-T angle in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64] This kind of relationship between QRS-T angle and cardiac autonomic neuropathy may suggest structural, functional, and electrical imbalance. 65 Furthermore, spatial QRS-T angel >45-50 degrees in T2DM increased the risk of incidents of cardiovascular disease by 114% total mortality increase by two folds 33 and the morbidity of silent myocardial infarction by 19%. 66 Although FQRSTA derived from planar ECG and spatial vector may be used to estimate the prognosis and morbidity of cardiac diseases mentioned above; we have not yet analyzed the influence of FQRSTA from Holter on prognosis or diagnosis of cardiac diseases in this study.…”
Section: Dm and Fqrstamentioning
confidence: 99%
“…41 FQRSTA is a very powerful predictor of cardiovascular events (e.g., myocardial ischemia), 42 sudden cardiac death, [13][14][15][16][17]43 appropriate ICD therapy, 44,45 all-cause mortality, 15,[33][34][35][36][37] increased cardiac-related hospitalizations, 17,35 reduced left ventricular function, [34][35][36]46 especially in patients with postinfarction, [13][14][15][16][17] acute myocardial infarction with LVEF ࣘ40%, 47 the elderly, 12 chronic dialysis, [18][19][20] heart failure with preserved ejection fraction, 17 and ischemic stroke 48 considered stronger than any of the classical cardiovascular risk factors. 16,17 Risk factors leading to an elevation in FQRSTA were related to coronary artery disease, dialysis, poor-controlled hypertension, 49,50 pulmonary arterial hypertension, 51 left/right ventricular hypertrophy, 51-54 dilated left ventricle, 55 lower LVEF, 56 DM, 57, 58 smoking, [57][58][59] and female gender.…”
Section: Dm and Fqrstamentioning
confidence: 99%